Developing Integrated Program To Empower Society In Supporting Children’s Literacy Practices: An Overview From A Village In Indonesia - Endah Silawati; Tita Mulyati (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2021)
Literacy skills of Indonesian students in every level are still low compared to other ASIAN countries. To overcome this problem, Indonesian government has developed many programs in improving literacy skills. However, the program has not given significant result since it is only done in formal school. Whereas current studies show that children developed the embryonic knowledge that leads to official literacy skills in their early childhood period at home and Early Childhood Education centre long before they enter formal school. Therefore, it is needed comprehend studies of early literacy development program in Indonesian setting involving the family and society to improve the literacy skills of the children. Therefore, this study describes strategies to strengthen literacy practices for children at home setting and society in one of Indonesian villages through Participatory Action Research (PAR) method. Focus group discussion (FGD) which involved 30 parents, 3 kindergarten teachers and 3 childrens as participants becomes the main technique in gathering the data. In addition, interview was also conducted to get deeper information from particular participant. Furthermore, based on FGD, there are some factors that could strengthening literacy practices for the children such as, good library facilities, varied and sustainable library programs, improving parents’ skills on literacy stimulation techniques for children and providing literacy community at rural area level. Moreover, as a result of FGD activities, the participants and facilitators developed a program called “Pohon Literasi (Literacy Tree).” Then, this program was implemented in three cycles. Each cycle took one week period of implementation. In conclusion, this program could increase reading interest of children and family members.